Unexpected prolapse of the anterior leaflet during saline testing in mitral valve repair. (21st September 2018) - Olsthoorn, Jules R; Heuts, Samuel; Streukens, Sebastian A F; Hermans, Sem M M; Maessen, Jos G; Sardari Nia, Peyman
Abstract: OBJECTIVES: Saline testing is used in mitral valve (MV) surgery to evaluate the repair intra-operatively. Sometimes, saline testing shows a prolapse of the anterior leaflet, not seen on preoperative echocardiography. Our objective was to investigate the incidence, predisposing factors and consequences of this phenomenon. METHODS: We retrospectively reviewed all consecutive patients undergoing surgery for posterior leaflet prolapse between 2013 and 2017. All data, including intraoperative video recordings of the repair and saline testing, were collected prospectively. RESULTS: Isolated posterior leaflet repair was performed in 91 patients. In 17 patients (18.7%), saline testing showed an unexpected anterior leaflet prolapse. Patients with unexpected prolapse presented with higher body mass index (BMI) compared to the reference group (27.5 ± 2.3 vs 25.0 ± 4.2, P = 0.01). Binomial logistic regression analysis showed BMI, surgical approach, number of prolapsing segments, left ventricular ejection fraction, left ventricular end systolic diameter and left atrial diameter to be predictive for unexpected anterior leaflet prolapse. In patients with unexpected anterior leaflet prolapse, no adequate saline testing was possible and repair was accomplished based on correction of the prolapse as seen on a preoperative echocardiogram. In both groups, 100% repair rate was achieved. Predischarge mitral regurgitation grading showed mild or less mitral regurgitation in all the patients in the unexpected prolapse group in comparison with 98.6% of patients in the reference group. CONCLUSIONS: When saline testing shows an unexpected prolapse of the anterior leaflet, not present on preoperative echocardiography, no additional surgical techniques should be performed in order to achieve an excellent postoperative result. Further research is warranted to predict unexpected anterior leaflet prolapse preoperatively.